2021
DOI: 10.1111/jch.14397
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approach to predicting albuminuria in persons with type 2 diabetes: An analysis of the LOOK AHEAD Cohort

Abstract: Albuminuria and estimated glomerular filtration rate (e‐GFR) are early markers of renal disease and cardiovascular outcomes in persons with diabetes. Although body composition has been shown to predict systolic blood pressure, its application in predicting albuminuria is unknown. In this study, we have used machine learning methods to assess the risk of albuminuria in persons with diabetes using body composition and other determinants of metabolic health. This study is a comparative analysis of the different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…These, too, were in keeping with previous findings. Duration of diabetes was an unmodifiable risk factor of ACR in patients with T2DM ( 41 ) while a high protein diet can exacerbate hypertension and expedite glomerular damage ( 42 ). Additionally, our results showed central obesity and a higher Na/K intake ratio could impose an extra burden on the kidney in patients with T2DM who had HbA1c ≥ 6.4%.…”
Section: Discussionmentioning
confidence: 99%
“…These, too, were in keeping with previous findings. Duration of diabetes was an unmodifiable risk factor of ACR in patients with T2DM ( 41 ) while a high protein diet can exacerbate hypertension and expedite glomerular damage ( 42 ). Additionally, our results showed central obesity and a higher Na/K intake ratio could impose an extra burden on the kidney in patients with T2DM who had HbA1c ≥ 6.4%.…”
Section: Discussionmentioning
confidence: 99%
“…To train models to predict DKD, 8 demographic and clinical risk factors linked to diabetic kidney disease were used as predictors, based on previous studies [ 2 , 7 , 10 ], and they were extracted from the hospital’s electronic medical records system, including: age, gender, duration of diabetes, hypertension, history of cardiovascular and cerebrovascular disease, smoking, BMI (kg/m 2 ), and glycosylated hemoglobin (%). Hypertension was defined as systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg, self-reported physician-diagnosed hypertension or use of blood pressure-lowering medications.…”
Section: Methodsmentioning
confidence: 99%
“…Early detection of diabetic kidney disease will allow appropriate interventions and thus substantially reduce the health-care burden. Detection of diabetic kidney disease depends on measurement of albuminuria or estimated glomerular filtration rate (eGFR) [ 2 ], but increasing evidence has shown that some DKD patients will not develop albuminuria [ 3 ]. Moreover, the measurements of albuminuria or eGFR are not always convenient since serum or urine samples need to be obtained and they have limited precision at an earlier DKD stage [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI has been applied to ten populations of patients with type 2 diabetes to predict development of DN using various combinations of demographics, vital signs, and laboratory tests. [83][84][85][86][87][88][89][90][91][92] The predictions were compared with modified databases in a sensitivity analysis comparison in two of these reports 84,87 and outperformed algorithms derived exclusively from clinical data in four of these reports. 83,85,86,91 In addition to standard data extraction, one study used natural language processing to identify data from the EHR.…”
Section: Technology Needed To Improve the Use Of Ai To Diagnose Diabe...mentioning
confidence: 99%